Differing isomerization kinetics of azobenzene-functionalized self-assembled monolayers in ambient air and in vacuum - Moldt, Thomas; Przyrembel, Daniel; Schulze, Michael; Bronsch, Wibke; Boie, Larissa; Brete, Daniel; Gahl, Cornelius; Klajn, Rafal; Tegeder, Petra; Weinelt, Martin (Langmuir, 2016)
Azobenzenealkanethiols in self-assembled monolayers (SAMs) on Au(111) exhibit reversible trans-cis photoisomerization when diluted with alkanethiol spacers. Using these mixed SAMs, we show switching of the linear optical and second-harmonic response. The effective switching of these surface optical properties relies on a reasonably large cross section and a high photoisomerization yield as well as a long lifetime of the metastable cis isomer. We quantified the switching process by X-ray absorption spectroscopy. The cross sections for the trans-cis and cis-trans photoisomerization with 365 and 455 nm light, respectively, are 1 order of magnitude smaller than in solution. In vacuum, the 365 nm photostationary state comprises 50-74% of the molecules in the cis form, limited by their rapid thermal isomerization back to the trans state. In contrast, the 455 nm photostationary state contains nearly 100% trans-azobenzene. We determined time constants for the thermal cis-trans isomerization of only a few minutes in vacuum and in a dry nitrogen atmosphere but of more than 1 day in ambient air. Our results suggest that adventitious water adsorbed on the surface of the SAM stabilizes the polar cis configuration of azobenzene under ambient conditions. The back reaction rate constants differing by 2 orders of magnitude underline the huge influence of the environment and, accordingly, its importance when comparing various experiments.